Aripiprazole versus haloperidol in combination with clozapine for treatment-resistant schizophrenia: a 12-month, randomized, naturalistic trial. - Cipriani, A; Accordini, S; Nosè, M; Purgato, M; Girlanda, F; Tansella, M; Barbui, C (2013)
BACKGROUND: Long-term studies for patients with resistant schizophrenia are necessary to assess the effectiveness of combination strategies on persisting positive symptoms. AIMS AND METHODS: This multicenter, naturalistic, randomized, superiority study (ClinicalTrials.gov identifier: NCT00395915) aimed to compare clinical efficacy and tolerability of haloperidol versus aripiprazole as combination treatment with clozapine in patients with resistant schizophrenia. RESULTS: One hundred six patients were followed up for 12 months. After 12 months, the proportion of patients who discontinued treatment was not significantly different between aripiprazole and haloperidol (37% vs 28%, respectively; P = 0.431). The change in the Brief Psychiatric Rating Scale score was similar in the aripiprazole and haloperidol groups (-7.0 vs -7.9, respectively; P = 0.389), whereas the tolerability total score decreased significantly more in the aripiprazole group (-7.2 vs -2.3; P = 0.008). CONCLUSIONS: While the effectiveness of clozapine augmentation with a second antipsychotic agent is not clearly demonstrated yet, results from this study suggest that augmentation with aripiprazole offers no substantial benefit over haloperidol in efficacy. Aripiprazole was perceived more tolerable than haloperidol, but it is uncertain how this finding may translate into the real world of clinical practice.